Pengaruh upah, pertumbuhan ekonomi dan kesempatan kerja terhadap jumlah pengangguran terdidik di Kabupaten Muaro Jambi Tahun 2001-2015 - Depi, Depi; Yulmardi, Yulmardi; Hardiani, Hardiani (Jurnal Paradigma Ekonomika, 2020)
This research aims to analyze the effect of wages, economic growth, and employment against the number of Educated Unemployment in Muaro Jambi Regency period 2001-2015. This research is a quantitative research using time series data from the years 2001-2015. The type of data used in this research is secondary data obtained from the Badan Pusat Statistik of Jambi Province. The results showed that the wages and employment opportunities have a significant influence on the number of educated unemployment in Muaro Jambi Regency, but economic growth has not significantly influenced the number of educated unemployment in Muaro Jambi Regency years 2001-2015. The regression results show that the value of RÂ² the independent variable (wages, economic growth, and employment opportunities) has a value of 0,627091 which means 62,70 % number of educated unemployment affected by wages, economic growth, and employment opportunities. While remaining 37,30 % explained by variables other than the model.